Explaining the emergence of Boko Haram: state failure and relative deprivation - Mavhura, Bathromeu (Stellenbosch : Stellenbosch University, 2020)
For more than a decade, Boko Haram terror attacks, although not regular occurrences, have remained the greatest security threats in Nigeria, mostly in the north-east and in neighbouring countries in the Lake Chad Basin. The group has threatened social, economic and political stability, which in turn impedes economic development. Corruption, poverty, unemployment, and inequality remain acute in Nigeria, specifically in the north-east region in which Boko Haram attacks have been dominant and recurring. The study utilises desktop research and employs state failure and relative deprivation theory as the methodology and analytical framework to help explain the emergence and the rise of Boko Haram. The study examines how inequality, corruption, unemployment, and poverty have created fertile grounds for resentment and anger in Nigeria. It also examines the ways in which these factors have made it difficult to curb the terror attacks. The connection between state failure and relative deprivation and its links to terrorism are explored by linking the theory and the empirical evidence of bad governance, poverty, unemployment and human security inequalities in north-east Nigeria. The study contends that Nigeria as a whole should not be called a failed or a failing state. However, the north-east region falls under the umbrella of failed or failing state because of available evidence of the characteristics of a failed or failing state. There the extent of poverty and underdevelopment is relatively higher than other states in the Federal Republic of Nigeria. The study argues that the state's response to the Boko Haram problem has been the use of a heavy-handed military approach, with severe human rights violations and limited efforts to address the main causes of the crisis. This approach is combined with an absence of non-violent conflict resolution approaches such as negotiations. Regional and continental bodies have also made use of military interventions, while there have been fewer efforts to address the root causes. On a state level, the study argues that corruption, lack of political will, poor security mechanisms, and human rights abuses have worsened the situation and have made intervention efforts less effective. The regional and continental bodies also lacked the capacity and the common will to intervene timeously to resolve the crisis. The thesis concludes by recommending that the state and all parties involved embrace a ‘soft’ approach that aims to address the root causes of the problem in the north-eastern region, which Boko Haram has capitalised on, in order to garner support from the disgruntled youth.